Time-effect and instability behaviour of cohesive soils - Manish Tiwari (2010)
The stress-strain behaviour of cohesive soils is known to be affected significantly by time-effects such as shearing rate effects, creep and stress relaxation. Shearing rate may affect the shear strength and friction angle of soil. However, the mechanism behind the rate-effects is not well understood. The effect of loading mode, i.e. whether the test is conducted in load-controlled or deformation-controlled loading mode, has been seldom studied despite the fact that most of the field loading conditions are load-controlled, whereas the laboratory tests are mainly carried out using deformation-controlled loading mode. Undrained creep in clay, which is one of the major time related problems, is often studied in terms of axial strain rate at a given deviator stress. However, the variation of pore water pressure and effective stresses during undrained creep should be studied as well. Whether the instability will occur at a pre-failure state similar to that observed for sand is not yet known. It should be particularly mentioned that the study of time-effects in triaxial tests on Singapore marine clay has never been reported.